Odpowiedź:
zad 24
a)(a+b)-(2a-b)-(a-2b)
a+b-2a+b-a+2b
-2a+4b
b)(3x-y+1)-(x+y)+(y-x)
3x-y+1-x-y+y-x
-y+2x+1
c)-(kx+ny)-(3kx+2ny)+(5kx-3ny)
-kn-ny-3kx-2ny+5kx-3ny
-6ny-kn+2kx
d)(2ab+a+3)-(3ab-a+3)
2ab+a+3-3ab+a-3
2a-1ab
e)(4x^2-3x)-(x+0,1x^2)-(x^2-0,1x)
4x^2-3x-x-0,1x^2-x^2+0,1x
3,1x^2-3,9x
zad25
a)(x^2+1)-(x^2-x)+10 dla x=2,2
2,2^2+1-2,2^2+2,2+10
11
b)(a+4b)-(5+2a)-(3b-5) dla a=-0,1 b=0,2
-0,1+4*0,2-5-2*(-0,1)-3*0,2+5
-0,1+0,8-5-0,2+0,9+5
0,9+4,8+5,9
10,7+0,9
11,6
c)(-a^2+2ab-1)+(a^2-4ab+5) dla a=14 i b=2
-14^2+2*(14+2)-1+14^2-4(14+2)+5
32-1-64+5
-28
Szczegółowe wyjaśnienie: